Executive Committee Minutes 2018-11-01 - Academic Senate:::::::::
Agenda Approved. Minutes of 10/18/18 Approved. From SAC & AAS: Template for Admissions Criteria for Majors – no action from Ex Com. Revision to the Human Development Major – Approved for consent calendar. Revision to Liberal Studies – Ukiah, Napa, Solano – Approved for consent calendar. Information item: Program Re-organization Gerontology. Chair Report. President's Report. Provost's Report. Statewide Senator Report. ECSE – Added Authorization to Specialist Credential – Approved for consent calendar. Revision to the Emeritus Policy – referred back to FSAC. Vice Chair Report. Vice President of Administration and Finance report. APARC Report. EPC Report. FSAC Report. Associated Students Report. Senate Agenda approved.